The Impact of Work-Life Balance and Workload on Task Performance through Organizational Commitment at PT. Bank Rakyat Indonesia, Pare Branch - Sofiana, Putri; Jatmiko, Udik; Ambarwati, Diana (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
The research aims to determine impact of work-life balance and workload on task performance through organizational commitment at PT. Bank Rakyat Indonesia, Pare Branch. This study employed a quantitative approach with 47 employees from Bank Rakyat Indonesia Pare Branch as the research subjects and as the research object using non-probability sampling techniques. Data collection techniques included observation, questionnaires, interviews, and literature review. Data analysis was conducted using the Partial Least Squares (PLS) method, utilizing Smart PLS 4.0 software. The results show that work-life balance and workload have no significant direct impact on task performance. However, organizational commitment significantly influences task performance and mediates the relationship between workload and task performance. Conversely, organizational commitment does not mediate the relationship between work-life balance and task performance. These results highlight the importance of managing workload and work-life balance to optimize employee performance.